Surgical Management of Urolithiasis in Male Dogs: A Clinical Review of 10 Cases - Shah, Mudasir Ahmad; Bhat, Abas Rashid; Basha, Mohamad Artf; Saxena, Abhishek (Indian Journal of Veterinary Sciences and Biotechnology, 2018)
Urolithiasis poses an acute life threatening emergency and most frequently obstructs the lower urinary tract in male dogs (Franti et al., 1999). It has been reported that the upper urinary tract calculi are uncommon in dogs and cats with majority of uroliths (Osborne and Fletcher, 1995). The most probable causes include infections, nutritional deficiencies and mineral imbalances. The mineral deposits which form in the bladder of male dogs get flushed out of the bladder with urine and lodge in the penis just behind the os penis which is the most commonly reported site of obstruction followed by ischial arch (Franti et al., 1999). Diagnostic imaging techniques like radiography and ultrasonography are sensitive in diagnosis, with abdominal ultrasonography having 90% sensitivity, 98% specificity and 97% accuracy (Webb, 2000). Treatment of urolithiasis can be attempted by retrograde urethral hydropropulsion for urethroliths followed by cystotomy (Osborne et al., 1999), failing of which urethrotomy or urethrostomy is indicated (Smeak, 2000). Other techniques like bladder marsupialization, surgical tube cystostomy and minimal invasive surgical tube cystostomy with their short and long-term complications have been attempted. However, in this study the cases were relieved by retrograde urethral hydropropulsion, cystotomy and urethrotomy.